Marine Propellers and Propulsion (3rd Edition) - Carlton, J. S. (Elsevier, 2012)
Propulsion technology is a complex, multidisciplinary topic with design, construction, operational and research implications. Bringing together a wealth of disparate information from the field, this book provides comprehensive and cutting edge coverage to equip marine engineers, naval architects and anyone involved in propulsion and hydrodynamics with the knowledge needed to do the job. Drawing on experience from a long and varied career in consultancy, research, design and technical investigation, author John Carlton breaks the subject into three main sections-hydrodynamic theory, materials and mechanical considerations, and design, operation and performance. Connecting essential theory to practical problems in design, analysis and operational efficiency, this is an invaluable resource, packed with hard-won insights, detailed specifications and data.